Taxonomic relationships of pollens from matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry data using multivariate statistics. (13th May 2015) - Seifert, Stephan; Weidner, Steffen M.; Panne, Ulrich; Kneipp, Janina
<x xml:space="preserve">Abstract</x> Rationale Matrix‐assisted laser desorption/ionization mass spectrometry (MALDI‐MS) has been suggested as a promising tool for the investigation of pollen, but the usefulness of this approach for classification and identification of pollen species has to be proven by an application to samples of varying taxonomic relations. Method MALDI‐MS in combination with hierarchical cluster analysis (HCA) and principal component analysis (PCA) was used to delineate taxonomic relations between plants based on pollen biochemistry. To assess the robustness of the approach, pollen of 74 species of the plant orders Fagales and Coniferales were probed. Results Discrimination at the levels of plant order and genus were achieved using the whole spectral range. In many cases, different species of the same genus could be distinguished. The sources of the spectral/chemical differences at the genus level can be understood using PCA. Specifically, typical mass regions for exact genus detection were identified. Conclusions Our results indicate that the chemical information represented by MALDI‐TOFMS data is useful for reconstructing taxonomic relationships and is complementary to other chemical information on pollen from other spectroscopic data. Copyright © 2015 John Wiley & Sons, Ltd.